Glycocalyx degradation: exploring related mechanisms, pathophysiological significance, and therapeutic prospects - Yuwen Tian; Quan Zheng; Jiaxin Yin; Tian Liu; Wufeng Zhang; Yu Ban; Lisha Zheng; Wen Tang; Hongyan Kang (Journal of Physiology and Biochemistry, 2026)

Environmentally relevant concentrations of DCOIT impaired lifespan and healthspan in Caenorhabditis elegans - Xiaoyu Zhu; Yahui Shang; Heng Ni; Yuwei Wang; Chuang Ban; Zhenyan Cui; Sitong Dong; Yu Shi; Dajing Xia; Yihua Wu (Journal of Environmental Sciences, 2026)

Thermally induced self-assembly of zein into amyloid fibrils under alkaline-ethanol conditions: Kinetics, structural evolution, and molecular interactions - Hao Liu; Wucongqi Ban; Jingjing Fu; Yan Liu; Ying Liang; Xia Zhang; Yingtao Yu; Xiaohua Wang; Jinshui Wang (Food Chemistry, 2026)

CO2 sequestration via mixed hydrate formation in depleted Class I, II, and III hydrate reservoirs: A comparative study from laboratory to field scale - Hongyu Ye; Ling-ban Wang; Jie Li; Daoyi Chen; Xuezhen Wu; Dayong Li; Guang-jin Chen; Chang-yu Sun; Mucong Zi (Chemical Engineering Journal, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Development of a prototype system for a rice yield prediction using deep learning - Ho-Young Ban; Seo-Young Yang; Ju-Hee Kim; Jae-Kyeong Baek; Yeong-Seo Song; Yu-Na Kim; Kyung-Do Lee; Sera Jo; Kyo-Moon Shim; Suk-won Roh; Miok Eom; Jiyoung Shon; et al. (Journal of Crop Science and Biotechnology, 2026)

Multi-technique NMR analysis of liquid CO2 hydrate growth and pore structure evolution in sediments - Yu-Hao Bu; Yi-Fei Sun; Xiao-Cun Ma; Ling-Ban Wang; Zhen-Bin Xu; Yong-Yi Zhai; Jin-Rong Zhong; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The impact of the carbon structure of oil-based collectors on the flotation performance and bubble adhesion mechanisms of microfine flake graphite: a comparative study of n-alkanes and n-alkylbenzenes - Jianwei Yu; Wanzhong Yin; Jin Yao; Bin Yang; Daolai Tian; Taozhong Zhang; Weifan Du; Xiaoqi Ban; Dilinuer Abudukade (Minerals Engineering, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Full-Length Transcriptome Analysis of the Pituitary of Pre-Matured and Artificially Matured Female Japanese Eel (Anguilla japonica) - Yu Gao; Jiangling Li; Zhenguang Feng; Mingxi Huang; Wen Li; Ruihan Xu; Ruoxue Chen; Yu Ban; Jingjie Liang; Yan Huang; Yangjie Xie; Jianchun Chen; et al. (Journal of Ocean University of China, 2026)

Flavonoids from the whole plants of limonium sinense and their anti-inflammatory activity - Ban-Ban Li; Shao-Wei Sun; Shuang Miao; Li-Juan Yang; Xin-Yu Meng; Kai-Kai Gong; Shi-Zhou Qi; Jin-Jie Zhang (Natural Product Research, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Chronic ethanol exposure reduces resting state functional connectivity and regional synchrony in male rats - Elizabeth J. Crofton; Sung-Ho Lee; Woomi Ban; Tzu-Wen Winnie Wang; Yen-Yu Ian Shih; A. Leslie Morrow; Melissa A. Herman (Psychopharmacology, 2026)

Hierarchical macro–mesoporous oxides and carbon materials via homopolymer-assisted dual phase separation - Jongyoon Park; Ji Sung Park; Jiwoo Lee; Jiyun Lee; Dongyoon Woo; Minkyeong Ban; Seongseop Kim; Eunho Lim; Jinyoung Chun; Sungju Yu; Chung-Yul Yoo; Jonghee Yoon; et al. (Chemical Engineering Journal, 2026)

A supply-flow-demand network framework for unraveling the compounded impacts of future climate and functional space on urban water-soil ecosystem services - Yu Wang; Junfei Chen; Tonghui Ding; Yufei Han; Xiaodong Yan; Jiayuan Guo; Qingqing Ban; Ting Cheng (Sustainable Cities and Society, 2026)

Temperature-pressure field evolution of hydrate-bearing sediments: A comparative study of depressurization strategies for gas recovery using a novel fan-shaped simulator - Ling-Ban Wang; Yi-Fei Sun; Yu-Hao Bu; Zhen-Bin Xu; Xian Sun; Han-Feng Shao; Chang-Yu Sun; Guang-Jin Chen (Gas Science and Engineering, 2026)

Research progress and future prospects of smellscape: a bibliometric analysis - Yu Ban; Jianfei Chen; Xiang Wang; Xiaolu Zhou; Xinyi Bei (Landscape and Ecological Engineering, 2026)

Enhancing cold storage quality of ‘Muscat Hamburg’ grapes: SO2 slow-release preservative and aroma dynamics - Jie Ren; Pufan Zheng; Jinze Yu; Na Zhang; Liya Liang; Zhaojun Ban; Arzu Şen; Yuyun Lu; Cunkun Chen; Xiaoxue Li (Food Control, 2025)

Effect of upper seawater infiltration on submarine natural gas hydrate exploitation: using a pilot-scale fan-column simulator - Ling-Ban Wang; Yi-Fei Sun; Yu-Hao Bu; Zhen-Bin Xu; Xian Sun; Han-Feng Shao; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Research On the Treatment of Phenol Wastewater By Persulfate Activation Based On Heterogeneous Catalyst CoFe2O4 - Fuchen Ban; Jingyi Su; Xueting Zheng; Yu Wei; Ao Xiao (Water, Air, & Soil Pollution, 2025)

Elucidation of chemosensory and neurophysiological approaches of rice (Oryza sativa L.) bran foods with sugar substitutes through permutation and machine learning-assisted screening methods - Hyeonjin Park; Younglan Ban; Seong Jun Hong; Se Young Yu; Hee Sung Moon; Eui-Cheol Shin (Food Bioscience, 2025)

Precise identification of faults research based on expanding frequency seismic data - Si Guo; Hai-Sang Ban; Tian-Wen Hu; Chong Han; Yu Peng; Di Zhao; Zong-Wei Wu (Applied Geophysics, 2025)

A temporal-segmentation-and-fusion-based large-scale constrained multi-objective evolutionary algorithm for coal mine integrated energy systems dispatch - Xuanxuan Ban; Jing Liang; Dunwei Gong; Yong Zhang; Yaonan Wang; Canyun Dai; Kangjia Qiao; Kunjie Yu (Swarm and Evolutionary Computation, 2025)

Multifunctional surface-enhanced Raman scattering imaging for detection and visualization of pesticide residues in crops - Xiaotong Wang; Xiaomeng Sun; He Huang; Yujiang Huang; Yue Zhao; Zhehan Liu; Shen Jiang; Yunpeng Wang; Tao Ban; Yu Liu; Yang Li (Journal of Hazardous Materials, 2025)

Achieving efficient freshwater generation and triboelectric collection based on an integrated device empowered by solar and wave energy - Xiangyu Cheng; Qingyu Geng; Li Yang; Ruliu Yan; Haoyang Ban; Jiahui Zhou; Fang Yu; Qinfang Zhang (Journal of Environmental Chemical Engineering, 2025)

Antioxidant and chemosensory properties of rice (Oryza sativa L.) bran under different oven-roasting conditions - Hyeonjin Park; Younglan Ban; Seong Jun Hong; Sojeong Yoon; Hee Sung Moon; Se Young Yu; Eui-Cheol Shin (Food Chemistry, 2025)

Sensomics and chemometrics approaches of differential brewed and roasted coffee (Coffea arabica) from Ethiopia using biomimetic sensory-based machine perception techniques: Effects of caffeine on bitter taste and the generation of volatiles - Younglan Ban; Hyeonjin Park; Seong Jun Hong; Se Young Yu; Hee Sung Moon; Eui-Cheol Shin (Food Chemistry, 2025)

Development of a novel eco-friendly depressant for the selective flotation of magnesite from dolomite: Investigation of Luteolin’s effectiveness and mechanism of action - Xiaoqi Ban; Jin Yao; Wanzhong Yin; Weifan Du; Taozhong Zhang; Yu Xie; Wenju Sun; Yulian Wang (Process Safety and Environmental Protection, 2025)

Temperature and wind speed help fermentation-sourced microbiota reconstruct the airborne microbiota in the Chinese baijiu fermentation region - Yifu Zheng; Yingli Jiang; Jiao Niu; Wanyu Deng; Shibo Ban; Yan Xu; Qun Wu; Yu Shi (Journal of Environmental Management, 2025)

Effects of static magnetic field treatment on the digestive, structural and physicochemical characteristics of germinated corn starch - Xin Jiang; Fangzhu Zheng; Jiankun Yu; Pengwen Lv; He Ban; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2025)

Thermo-reversible gel synthesized by 4-α-glucanotransferase with sol-gel transition tuned by subtle amylose manipulation - Yu Xiao; Haocun Kong; Zihang Jiang; Caiming Li; Xiaofeng Ban; Zhengbiao Gu; Zhaofeng Li (Food Hydrocolloids, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Elemental Imbalances After Manganese Exposure and the Regulatory Potential of Curcumin - Hua Zhao; Jia-Min Zeng; Yao Li; Chun-Yan Ao; Duo Liu; Jing-Peng Zhuo; Chun Yu; Jia-Qi Ban; Jun Li (Biological Trace Element Research, 2025)

Investigation of non-volatile and volatile compound profiles in Arabica coffee extracts and neurophysiological effects of different chemosensory stimulation according to sex: Insights from electronic sensors, EEG, and sLORETA approaches - Seong Jun Hong; Sojeong Yoon; Younglan Ban; Hyeonjin Park; Hee Sung Moon; Se Young Yu; Moon Yeon Youn; Daeyong Shin; Kiseong Kim; Young Jun Kim; Jae Kyeom Kim; Eui-Cheol Shin (Food Chemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Selective adsorption of eco-friendly inhibitor sesbania gum on dolomite for efficient flotation separation of magnesite and dolomite - Xiaoqi Ban; Jin Yao; Wanzhong Yin; Yu Xie; Taozhong Zhang; Weifan Du; Yulian Wang (Process Safety and Environmental Protection, 2025)

Molecular basis of E93-dependent tissue morphogenesis and histolysis during insect metamorphosis - Mei Zeng; Zi-Yu Yan; Ya-Nan Lv; Jia-Ming Zeng; Ning Ban; Dong-Wei Yuan; Sheng Li; Yun-Xia Luan; Yu Bai (Insect Biochemistry and Molecular Biology, 2025)

Explainable artificial intelligence framework for plastic hinge length prediction of flexural-dominated steel-reinforced concrete composite shear walls - Chaochao Quan; Wei Wang; Kuahai Yu; Danmei Ban (Engineering Structures, 2025)

An archive-assisted multi-modal multi-objective evolutionary algorithm - Peng Chen; Zhimeng Li; Kangjia Qiao; P.N. Suganthan; Xuanxuan Ban; Kunjie Yu; Caitong Yue; Jing Liang (Swarm and Evolutionary Computation, 2024)

Predicting the removal efficiency of titanium dioxide nanoparticles in an activated sludge system using fate modeling depending on the operating conditions - Min Jeong Ban; Hannah Mae Portus; Byung-Tae Lee; Yu Sik Hwang; Keugtae Kim; Joo-Hyon Kang (Journal of Water Process Engineering, 2024)

The application of KMnO4 in reverse flotation separation of chalcopyrite and talc and its selective depression mechanism - Yu Xie; Xiaoqi Ban; Wanzhong Yin; Ningbo Song; Jin Yao (Journal of Environmental Chemical Engineering, 2024)

Tetraphenylborate enhanced enzymatic production of γ-cyclodextrin: System construction and its mechanism - Zihang Jiang; Yu Xiao; Zhengyao Xu; Zhengbiao Gu; Zhaofeng Li; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Carbohydrate Polymers, 2024)

Evaluating urban development and socio-economic disparity in India through nighttime light data - Jingtong Yu; Lingcen Liu; Yifang Ban; Qian Zhang (Journal of Geographical Sciences, 2024)

Predicting the risk of arsenic accumulation in soil-rice system in Asian monsoon region - Ruxin Ban; Linsheng Yang; Jiangping Yu; Binggan Wei; Shuhui Yin (Science of The Total Environment, 2024)

Optimizing cropland use to reduce groundwater arsenic hazards in a naturally arsenic-enriched grain-producing region - Shuhui Yin; Linsheng Yang; Jiangping Yu; Ruxin Ban; Qiqian Wen; Binggan Wei; Zhiwei Guo (Journal of Environmental Management, 2024)

Mechanisms of enhancing MgO for stabilization/solidification of Pb-contaminated red clay through CO2 sequestration - Rulong Ban; Fusheng Zha; Bo Kang; Shan Wu; Yu Song; Hongbin Chen (Journal of Environmental Management, 2024)

MoS2@ZIF-8-based aerogel with multiscale biomimetic structure achieving all-day desalination and wastewater purification - Liu Zhang; Li Yang; Xiangyu Cheng; Jiahui Zhou; Haoyang Ban; Zihe Chen; Fang Yu; Xianbao Wang; Qinfang Zhang (Chemical Engineering Journal, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

Investigating the impact of control strategies on the sulfur dioxide emissions of South Korean industrial facilities using an aircraft mass balance approach - Gracie Wong; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; Beom-Keun Seo; et al. (Atmospheric Environment, 2024)

Application and mechanism of an efficient hydrophobic flocculant CPAM in the flocculation reverse flotation of hematite and microfine-grained chlorite - Yu Xie; Wanzhong Yin; Jin Yao; Feijia Xue; Jiayi Liu; Xiaoqi Ban (Journal of Environmental Chemical Engineering, 2024)

A recombinant amylomaltase from Thermus thermophilus STB20 can tailor the macromolecular characteristics of tapioca starch through its transglycosylation activity - Yu Xiao; Haocun Kong; Ziqian Zhang; Caiming Li; Xiaofeng Ban; Zhengbiao Gu; Zhaofeng Li (Food Bioscience, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

Geochemical relationships between shells of the gastropod Gyraulus convexiusculus and modern water bodies on the Tibetan Plateau, and their paleoenvironmental significance - Feng Chen; Jiao-Yan Zhao; Jiao Ren; Jin-Liang Feng; Hai-Ping Hu; Feng-Mei Ban; Le-Le Pei; Yu-Zhi Zhang; Kun-Ying Wang (Quaternary Science Reviews, 2024)

Velocity-Dependent Effect on the Peak Shear Strength of Rock Joints Considering the Distribution Characteristics of Contact Joint Surface - Liren Ban; Weisheng Du; Dong Zheng; Yuhang Hou; Chengzhi Qi; Jin Yu; Chun Zhu; Chunsheng Lu (Rock Mechanics and Rock Engineering, 2024)

Corrigendum to “Optimizing an airborne mass-balance methodology for accurate emission rate quantification of industrial facilities: A case study of industrial facilities in South Korea” [Sci. Total Environ. vol. 912, 169204] - Gracie Wong; Hui Wang; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; et al. (Science of The Total Environment, 2024)

Optimizing an airborne mass-balance methodology for accurate emission rate quantification of industrial facilities: A case study of industrial facilities in South Korea - Gracie Wong; Hui Wang; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; et al. (Science of The Total Environment, 2024)

A new eudesmane-type sesquiterpene and other constituents from Chloranthus henryi hemsl. var. hupehensis (Pamp.) K.F.Wu and their chemotaxonomic significance - Yun-He Zou; Ning Wang; Hui Yang; Yu-Hang Ban; Huan Liu; Hang Liu; Xiao-Xia Wang; Peng-Yu Zhuang (Biochemical Systematics and Ecology, 2024)

Concentration Dependence of the Diffusion Coefficient During Adsorption of Methane into Partially Water-Saturated Crushed Shale - Wentao Ban; Qingchun Yu (Natural Resources Research, 2024)

Influence of soil properties and near-surface roots on soil infiltration process in short-rotation eucalyptus plantations in southern subtropical China - You Huang; Tao Xiong; Mingquan Zhao; Yusong Deng; Gairen Yang; Yunyun Ban; Tingwu Lei; Xinxiao Yu; Yuhan Huang (CATENA, 2024)

A method to predict the peak shear strength of rock joints based on machine learning - Li-ren Ban; Chun Zhu; Yu-hang Hou; Wei-sheng Du; Cheng-zhi Qi; Chun-sheng Lu (Journal of Mountain Science, 2023)

Low phosphorus promotes NSP1–NSP2 heterodimerization to enhance strigolactone biosynthesis and regulate shoot and root architecture in rice - Kun Yuan; Hao Zhang; Chaoji Yu; Nan Luo; Jijun Yan; Shuang Zheng; Qingliang Hu; Dahan Zhang; Liquan Kou; Xiangbing Meng; Yanhui Jing; Mingjiang Chen; et al. (Molecular Plant, 2023)

Self-assembled carrier-free nanomedicine suppresses tumor stemness to overcome the acquired drug-resistance of hepatocellular carcinoma - Huimin Lin; Qing Xu; Fang Zhang; Hualan Wu; Ben Hu; Guimei Chen; Xiaohua Ban; Xiaohui Duan; Meng Yu (Chemical Engineering Journal, 2023)

Changes of preferential flow in short-rotation eucalyptus plantations: field experiments and modeling - Mingquan Zhao; You Huang; Tingwu Lei; Yusong Deng; Gairen Yang; Yunyun Ban; Xinxiao Yu; Yuhan Huang (Journal of Hydrology, 2023)

Differences in selenium concentration and bioavailability between paddy and dryland soils of China: A study based on literature collection and field sampling - Yuanzhe Ma; Nanchun Zhang; Yanan Li; Haolin Zhao; Fei Zhou; Mingyue Xue; Lihui Lyu; Jing Yang; Yu Ban Man; Fuyong Wu; Dongli Liang (Journal of Hazardous Materials, 2023)

Green algae monitoring via ground-based GNSS-R observations - Wei Ban; Nanshan Zheng; Kefei Zhang; Kegen Yu; Shuo Chen; Qi Lu (GPS Solutions, 2023)
Outbreaks of harmful algal blooms (HABs) exhibit high frequency, large range and damage aggravation characteristics, but existing monitoring methods, such as artificial and optical near-infrared remote sensing, cannot accommodate these characteristics. We propose a new method for monitoring green algae using Global Navigation Satellite System Reflectometry (GNSS-R) observations. The basic principle states that changes in the seawater dielectric constant and sea surface roughness due to the emergence of green algae lead to an increase in brightness temperature, which can be inverted based on the reflection time delay waveform. Shipboard reflection waveform data collected during an Enteromorpha prolifera outbreak in the Qingdao sea area were used for model development and validation of the detection and estimation performance. The results indicated that the root mean square error of GNSS-R-based inversion of the green algae density was 6.74%, indicating the potential of GNSS-R technology for rapid preliminary monitoring of green algae. Moreover, the advantages of a low cost, short return time and no climatic limitations support GNSS-R technology as a new and efficient means of green algae monitoring.

Modified Hoek–Brown failure criterion for anisotropic intact rock under high confining pressures - Zefan Wang; Chengzhi Qi; Liren Ban; Hang Yu; Haonan Wang; Ziming Fu (Bulletin of Engineering Geology and the Environment, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Strength and electrical resistivity characteristic of carbonating reactive MgO-mixed red clay under different water contents - Rulong Ban; Xuejun Chen; Xin Yang; Jianqiang Wang; Zongyuan Pan; Yu Song (Arabian Journal of Geosciences, 2022)

Porcine circovirus type 3 capsid protein induces NF-κB activation and upregulates pro-inflammatory cytokine expression in HEK-293T cells - Xianhui Liu; Hanqin Shen; Xinming Zhang; Tairun Liang; Yanfang Ban; Linyang Yu; Leyi Zhang; Yanling Liu; Jianguo Dong; Pengfei Zhang; Kaiqi Lian; Changxu Song (Archives of Virology, 2021)

Time Delay Mechanism of the Kaiser Effect in Sandstone Under Uniaxial Compressive Stress Conditions - Xiang Fu; Yu-Xin Ban; Qiang Xie; Rini Asnida Abdullah; Jun Duan (Rock Mechanics and Rock Engineering, 2021)

Construction of high-density genetic maps defined sex determination region of the Y chromosome in spinach - Li’ang Yu; Xiaokai Ma; Ban Deng; Jingjing Yue; Ray Ming (Molecular Genetics and Genomics, 2021)

Noninvasive Simultaneous Diagnosis of Multiple Upper Respiratory Tract Diseases using Speech Signal Parameters - S. N. Kirillov; D. Yu. Mamushev; A. N. Kuchurkin; E. V. Ban’ (Biomedical Engineering, 2020)

Risk-stratified approach to anti-viral prophylaxis against cytomegalovirus disease in glomerulonephritis and renal vasculitis treated with potent immunosuppressants - Cynthia Ciwei Lim; Ban Hock Tan; Yu Tzu Tung; Huijun Huang; Ying Hao; Irene Y. J. Mok; Puay Hoon Lee; Jason C. J. Choo (Infectious Diseases, 2019)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Multi-angle Indicators System of Non-point Pollution Source Assessment in Rural Areas: A Case Study Near Taihu Lake - Lei Huang; Jie Ban; Yu Ting Han; Jie Yang; Jun Bi (Environmental Management, 2013)

Characteristics of nutrients in natural wetland in winter: a case study - Liang Zhang; Yun Du; Shengjun Wu; Cheng Yu; Qi Feng; Xuan Ban; Xianyou Ren; Huaiping Xue (Environmental Monitoring and Assessment, 2012)

Temperature trends in the skin/surface, mid-troposphere and low stratosphere near Korea from satellite and ground measurements - Jung-Moon Yoo; Young-In Won; Young-Jun Cho; Myeong-Jae Jeong; Dong-Bin Shin; Suk-Jo Lee; Yu-Ri Lee; Soo-Min Oh; Soo-Jin Ban (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Transgenic Amorphophallus konjac expressing synthesized acyl-homoserine lactonase (aiiA) gene exhibit enhanced resistance to soft rot disease - Huifang Ban; Xinli Chai; Yongjun Lin; Ying Zhou; Donghai Peng; Yi Zhou; Yulan Zou; Ziniu Yu; Ming Sun (Plant Cell Reports, 2009)

Marker-assisted characterization of Asian wheat lines for resistance to Fusarium head blight - Jian-Bin Yu; Gui-Hua Bai; Shi-Bin Cai; Tomohiro Ban (Theoretical and Applied Genetics, 2006)